2015
DOI: 10.1080/15476286.2015.1017217
|View full text |Cite
|
Sign up to set email alerts
|

ASH1 mRNP-core factors form stable complexes in absence of cargo RNA at physiological conditions

Abstract: Asymmetric ASH1 mRNA transport during mitosis of budding yeast constitutes one of the best-studied examples of mRNA localization. Recently, 2 studies used in vitro motility assays to prove that motile ASH1 mRNA-transport complexes can be reconstituted entirely from recombinant factors. Both studies, however, differed in their conclusions on whether cargo RNA itself is required for particle assembly and thus activation of directional transport. Here we provide direct evidence that stable complexes do assemble i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…They however, reached contradicting conclusions on the role of ASH1 mRNA itself, with one study concluding that the mRNA itself is essential for processivity under physiological conditions to stabilise the transport complex [ 45 ], whereas the other argued that the cargo mRNA is dispensable for in vitro processivity [ 44 ]. It therefore remains unclear if the RNA moiety is essential for transport in living cells [ 47 , 48 ].
Fig.
…”
Section: Motor Proteinsmentioning
confidence: 99%
“…They however, reached contradicting conclusions on the role of ASH1 mRNA itself, with one study concluding that the mRNA itself is essential for processivity under physiological conditions to stabilise the transport complex [ 45 ], whereas the other argued that the cargo mRNA is dispensable for in vitro processivity [ 44 ]. It therefore remains unclear if the RNA moiety is essential for transport in living cells [ 47 , 48 ].
Fig.
…”
Section: Motor Proteinsmentioning
confidence: 99%
“…Recent in vitroreconstitution and single-particle motility assays demonstrated that these three proteins together with the myosin chaperone She4p and myosin light chains are sufficient to support processive transport of ASH1 mRNA along actin filaments. [41][42][43] In addition to this core complex, the transport particle is loaded with the translational repressors Dhh1p, Khd1p, and Puf6p [44][45][46][47][48] that ensure translational silencing of the transcript during transport 49 (Figure 1(c)). To release translational repression, Khd1p and Puf6p become phosphorylated by the casein kinases Yck1p and Yck2p.…”
Section: Localization Elements In Eukaryotesmentioning
confidence: 99%
“…As She3p is constitutively bound to the type V myosin motor Myo4p, the resulting complex consists of ASH1 mRNA, She2p, She3p, and Myo4p (Figure (b)). Recent in vitro ‐reconstitution and single‐particle motility assays demonstrated that these three proteins together with the myosin chaperone She4p and myosin light chains are sufficient to support processive transport of ASH1 mRNA along actin filaments …”
Section: Actin‐dependent Transport Of Mrnasmentioning
confidence: 99%